Literacy dalam Pembelajaran Matematika - Herli Salim; Turmudi Turmudi; Suryadi Suryadi (Peneliti.net, 2021)
Mathematical literacy is an individual's capacity to identify and understand this world by playing the role of mathematics to build a strong stance, and involving mathematics according to individual needs as constructive, caring, and reflective citizens. both for the present life and for the life to come. With the target of mathematics literacy, if the learning that leads to the achievement of mathematics literacy has to change again, it is almost certain that mathematics literacy will not be achieved. The experience of participating in PISA since 2000, for every three years, Indonesian children are only satisfied with a math score of 371 (in 2000), 360 (in 2003), 391 (in 2006), 371 (in 2009), 375 (in 2009). in 2012), and 386 (2015) and 379 (2018); Indonesian children's mathematics achievement was ranked 39th out of 41 participating countries (in 2000), 38 out of 40 countries (in 2003), ranked 50 out of 57 participants (2006), ranked 61 out of 65 participating countries (in 2009) , ranking 64 out of 65 participants (in 2012), ranking 64 out of 70 countries (in 2015) while the average International mathematics score is 500.